EUSATfinder EUropean Space, Aerial and Terrestrial assets supporting first responders' operations - MediaGEO, Redazione (GEOmedia, 2025)
The purpose of the EUSATfinder is to provide an innovative integrated and scalable solution, to support decision maker actors in real-life during different operational phases (detection, preparedness, response, recovery and mitigation of emergencies) with particular focus to first responders’ activities in situ for a disaster management. The solution is based on a mobile operational centre (MOC) able to join in the proximity of the emergency area and to deploy several assets to support the operations: 1. a quick to deploy resilient communication infrastructure; 2. a fleet of heterogenous drones for mapping (integrated with Copernicus Emergency Management Service), for extended environmental surveillance and for people and asset localisation; 3. innovative equipment for first responders’ health monitoring and localisation (Galileo); 4. a distributed platform for First responder operations and citizens alerting management. Galileo adding an additional layer of security against spoofing are clearly new coming valuable services supporting drones’ operations (including U-space) for these emergency applications. Moreover, Copernicus data will be integrated with is-situ observations in the Mobile Operational Control (MOC).